Topical bromfenac transiently delays axotomy-induced retinal ganglion cell loss. (May 2019) - Rovere, Giuseppe; Nadal-Nicolás, Francisco M.; Sobrado-Calvo, Paloma; Villegas-Pérez, María P.; Vidal-Sanz, Manuel; Agudo-Barriuso, Marta
Abstract: Optic nerve axotomy in rodents allows detailed studies of the effect of different treatments on the survival of central nervous system neurons, the retinal ganglion cells (RGCs). Here we have analyzed the neuroprotective effect of topical bromfenac treatment, a nonsteroidal anti-inflammatory drug (NSAID) used in clinic to ameliorate post-operative inflammation, on axotomized rat RGCs. The left optic nerve of adult rats was subjected to optic nerve crush (ONC). Half of the rats were treated with a topical instillation of saline. On the other half, immediately after the surgery, 2 drops of bromfenac (0.09% Yellox; Bausch & Lomb) were instilled, and then every 12 h until analysis. Retinas in both groups were dissected 3, 5, 7, 9 and 14 days after ONC (n = 4–8/time point/group). Toxicity of bromfenac was assessed in intact retinas treated during 14 days (n = 6). Intact untreated retinas were used as control of the RGC population. RGCs were identified by Brn3a immunodetection and automatically quantified. Our results show that bromfenac does not cause RGC loss in intact retinas. In the injured groups, the number of RGCs at 7, 9 and 14 days after the lesion was significantly higher in treated vs. untreated retinas. To our knowledge this is the first report showing that a topical treatment with a NSAIDs delays axotomy-induced RGC loss and indicates that treatment with NSAIDs could be used as conjunctive therapy in diseases that proceed with optic nerve damage. Highlights: 3-5 Highlights. Topical treatment with bromfenac during 14 days is not toxic for retinal ganglion cells (RGCs). Bromfenac treatment delays RGC death triggered by optic nerve crush (ONC). RGC survival in bromfenac treated retinas is higher than in untreated retinas up to 14 days post-ONC.